PENGETAHUAN DAN SUMBER INFORMASI KESEHATAN REPRODUKSI REMAJA DI INDONESIA - BKKN, Iswarati (Program Studi Pendidikan Manajemen Perkantoran, 2011)
Survey of adolescents in 2009 represents a national survey, designed to produce estimates at theprovincial level. The survey was conducted in 33 provinces in Indonesia. The purpose of this surveyis to identify the knowledge and sources of information on adolescent reproductive health (ARH). Thenumber of respondents 22.877 with details teenage male 52.3 percent and 47.7 percent female. Theresults showed that the knowledge of adolescents on reproductive health has not been as expected.Average value of every teenager in Indonesia showed that the composite index value of adolescentreproductive health knowledge is 55.4 (range 0-100). Highest with the lowest difference of 26.5 indexpoints, with the highest range in Bali (68.3) and lowest in Central Sulawesi (41.8). For that we need toincrease adolescent knowledge about adolescent reproductive health, which include knowledge aboutpuberty, fertile period, pregnancy risk, age at f irst marriage, age of first childbirth, anemia, drugs,alcohol, HIV/AIDS, and other Sexually Transmitted Infections/STD.Adolescent reproductive health information sources received by adolescents also remains low.Average value of every teenager in Indonesia composite index value of information on adolescentreproductive health 49.4 (index range: 0-100), still far from the target set (85 percent). Differencebetween the highest and the lowest index of 25.3 points, with The highest ranges of Central Java(57.8) and lowest in Central Sulawesi (32.5). Various sources of information that can be empoweredto dissemination of reproductive health knowledge, ie from the schools, mass media, family planningfield worker, health field worker, and informal meetings. Knowledge about adolescent reproductivehealth must be provided to adolescents, as well as to teachers, workers (family planning, health),religious leaders and community leaders.